Student team achievement divisions technique to improve students’ behaviour engagement - Herjayanto, Fajar Arif ((JELE) Journal Of English Language and Education, 2018)
Student Team Achievement Divisions (STAD) is a teaching strategy where students work together in small groups on a structured activity and it is presumably able to improve students’ behaviour engagement and learning outcome. Collaborative learning and engagement (specifically behaviour engagement) are something considered important in learning, especially in language learning as they can promote the effectiveness of learning via active participation of students in the learning process. The data of this study were collected by using questionnaire, observation, interview and diary which used successively. The data analysis revealed that (1) STAD can improve students’ behaviour engagement (2) Difficulties of STAD when it was applied in enhancing students’ behaviour engagement. Taking sample of twenty one students divided into five small groups, the research was conducted by using classroom action research design. The results indicates that students in a class with caring atmosphere and supportive interaction managed by the teacher; who played active roles as prompter, participant, and/or tutor as well as addressed the students autonomy via group work activity, are engaged behaviourally to the instructional. In conclusion, the student team achievement divisions technique can be applied to enhance students’ behaviour engagement on the english class successfully. Keywords: Student Team Achievement Divisions, Students’ behaviour engagement.